Nilai Dan Kegunaan Ilmu Bagi Manusia - Suriana Suriana; Syamsul Rijal (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The value of knowledge is very important in the scientific journey, because it can give birth to the utilization of knowledge. This study wants to discuss more deeply the value and usefulness of science for humans in living life in this world. The method used in this study is a qualitative method using library research, namely by examining reading sources that have to do with the studies discussed, as well as by using document studies of previous research results related to the philosophy of science. Data collection is done by tracing reading books, scientific journals, digital libraries, and libraries. It was found that the value of science includes a deep understanding of the universe, humans, and the relationship between the two. The uses of science are that humans can change the face of the world to be more advanced, help humans solve problems more effectively, develop technology so that humans can change the way of working, the way of thinking, change the barriers of space and time, increase career opportunities and open doors for various professions.